The impact of social media interactivity of sports organizations on consumer loyalty - Yang, Jiafa; Bae, Juyong; Lee, Kyongmin (Journal of Asian Scientific Research, 2025)
Consumer loyalty in the social networking sites (SNSs) environment is influenced not only by basic engagement but also by various other factors. This study examines the impact of social media interactivity, such as user control, personalization, responsiveness, interestingness, and two-way communication, on consumer loyalty in the context of sports organizations. Using SPSS 30.0 and AMOS 29.0, a survey was conducted with 212 university students in South Korea, and structural equation modeling (SEM) was employed to analyze the data. Among the five dimensions of social media interactivity, user control, interestingness, and two-way communication positively influence consumers’ social presence, which subsequently has a significant impact on consumer loyalty. Furthermore, social presence has a stronger effect on consumer loyalty than relationship satisfaction. This study demonstrates the impact of social media interactivity of sports organizations on consumer loyalty and identifies the unique contribution of social presence to enhancing consumer loyalty. This study provides nuanced insights into the influence of social media interactivity on consumer loyalty within sports organizations. It helps sports organizations to develop appropriate strategies to strengthen their emotional connection with consumers.